2016
DOI: 10.1051/0004-6361/201629281
|View full text |Cite
|
Sign up to set email alerts
|

Intensity contrast of the average supergranule

Abstract: While the velocity fluctuations of supergranulation dominate the spectrum of solar convection at the solar surface, very little is known about the fluctuations in other physical quantities like temperature or density at supergranulation scale. Using SDO/HMI observations, we characterize the intensity contrast of solar supergranulation at the solar surface. We identify the positions of ∼10 4 outflow and inflow regions at supergranulation scales, from which we construct average flow maps and co-aligned intensity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
5
11
0
Order By: Relevance
“…While the classic idea that supergranulation has a convective origin has usually been dismissed due to the seeming lack of photometric intensity contrast at the corresponding scales at the surface (Langfellner et al 2016), helioseismology suggests that relative temperature fluctuations of approximately a few percent are present underneath the surface at such scales (Duvall Jr et al 1997), in line with our calculation in Sect. 4.2.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…While the classic idea that supergranulation has a convective origin has usually been dismissed due to the seeming lack of photometric intensity contrast at the corresponding scales at the surface (Langfellner et al 2016), helioseismology suggests that relative temperature fluctuations of approximately a few percent are present underneath the surface at such scales (Duvall Jr et al 1997), in line with our calculation in Sect. 4.2.…”
Section: Discussionsupporting
confidence: 83%
“…The physical origin of this supergranulation is widely debated (Rieutord & Rincon 2010). In particular, while the idea that supergranulation-scale flows may just be a manifestation of some form of thermal convection has a long history, it has often been dismissed due to the seeming lack of photometric intensity contrast at the same scales (Langfellner et al 2016). Besides, there is as yet no general consensus on local helioseismic estimates of the amplitude, depth and structure of subsurface flows on this scale (Nordlund et al 2009;Rieutord & Rincon 2010;Gizon et al 2010;Švanda et al 2013;DeGrave et al 2014;Švanda 2015) -or in fact on any scale larger than that (see, e.g., Hanasoge et al 2012;Gizon & Birch 2012;Hanasoge et al 2016;Greer et al 2015;Toomre & Thompson 2015;Greer et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a first step, we identified the supergranulation-scale convergence features in the QS regions at t = −13.6 h. The algorithm is described in Appendix D. Figure 5 shows the average of the 1129 features that were identified by this algorithm. The flow pattern consists of a core with horizontally converging flows surrounded by a ring of horizontal divergence (consistent with Langfellner et al 2016). As was also described by Langfellner et al (2016), the magnetic field distribution is offset in the retrograde direction relative to the flow pattern.…”
Section: Ensemble Average Flow Mapssupporting
confidence: 59%
“…The general agreement of the model presented here with the observations suggests an interaction between rising flux concentrations and the supergranulation pattern during the emergence process. Langfellner et al (2016) showed that the vertical magnetic field is stronger on the prograde side of quiet-Sun Fig. 4), and the black lines show the corresponding quantities as predicted by the model described in this section.…”
Section: Discussionmentioning
confidence: 75%
“…Amplitude and/or frequency variations have been found among nearly all types of nonstochastically excited pulsating variables: δ Sct (Breger et al 2012, Breger & Pamyatnykh 2006, Bowman & Kurtz 2014; γ Dor (Rostopchina et al 2013); β Cep (Pigulski & Pojmanski 2008), roAp (Balona et al 2013, Medupe et al 2015; classical pulsators such as high-amplitude δ Sct stars (Zhou & Jiang 2011, Khokhuntod et al 2011, Cepheids (Engle 2015), RR Lyrae (Chadid & Preston 2013), Miras and yellow supergiants (Percy & Yook 2014, Percy & Khatu 2014; white dwarfs (DBV; Handler et al 2003 and DAV;Bell et al 2015); GW Vir stars (Vauclair et al 2012), sdB stars (Kilkenny 2010, Langfellner et al 2012), and an extreme helium subdwarf (Bear & Soker 2014).…”
Section: Causes Of Amplitude/frequency Variationsmentioning
confidence: 99%